Selección de mejores prácticas preventivas para disminuir los tiempos no productivos debido a pega de tubería por empaquetamiento para la perforación en el Campo Castilla de Ecopetrol S.A. (2017)
In this project, the best practices are choosed to drilling new wells in the Castilla Field, based on Ecopetrol's experience in the operation of field, the stuck pipe by packing is one of the operationals problems with a high percentage event. With that being said, the project is developed in five stages. In the first stage, the Castilian field geologycal chapter is done, with the aim to get in context about the spatial and temporal position about this. Equally, its geologycal features are defined. In the second stage, the theoretical bases are reviewed. In which the types of stuck pipes are defined and the mechanical stuck is emphasized, punctually in the packing. This stage describes each cause that leads to packing, establishing the reason why it is presented, its warning signs and prevention according to the academy.